On the Comparison of Narcissistic, Antisocial, and Borderline Personality Traits among Addicted Prisoners, Non-Addicted Prisoners, and Normal Subjects - A Mohammadzadeh; S Aghayi (Research on Addiction, 2015)
Objective: This study aimed to compare narcissistic, antisocial, and borderline personality traits among addicted prisoners, non-addict prisoners, and normal subjects. Method: This study employed a causal-comparative research method, with a sample size of 180 participants including addicted prisoners, non-addicted prisoners, and normal individuals (60 participants in each group) of Miandoab city who were matched in terms of demographic characteristics. For data collection purposes, narcissistic personality inventory NPI-16, Millon antisocial inventory-III, and borderline personality inventory were employed. Results: The results showed that there was a significant difference between addicted prisoners and normal subjects and also between addicted prisoners and non-addicted prisoners in terms of narcissistic traits while no significant difference was obtained between the non-addicted prisoners and normal subjects. Conclusion: The comparison of the aforementioned groups contains important information for the prevention and treatment of addiction and crime prevention.